EmoWELL: effectiveness of a serious game for emotion regulation in emerging adulthood - Velert-Jiménez, Saray; Valero-Moreno, Selene; Gil-Gómez, José-Antonio; Pérez-Marín, Marián; Montoya-Castilla, Inmaculada (Frontiers in Psychology, 2025)
IntroductionEmerging adulthood represents a critical period for developing emotion regulation skills, as individuals face new roles and responsibilities while often employing maladaptive regulatory strategies. Given the increasing use of technology among emerging adults, this study evaluated emoWELL, a serious game designed to enhance emotion regulation during this developmental stage.MethodsUsing a quasi-experimental design, 114 university students in emerging adulthood (aged 18–25) were assigned to either an experimental group using emoWELL or a control group. Analyses included MANOVA, MANCOVA, hierarchical multiple regression, Reliable Change Index (RCI), moderation, mediation, and qualitative analyses of participants’ feedback.ResultsSignificant improvements were observed in the experimental group (Wilks’ λ = .68; F = 2.59; p = 0.003; η2 = .32), particularly in reducing expressive suppression strategy, emotional rejection, lack of emotional control, and overall emotion dysregulation. Mediation analyses revealed that enhanced emotion regulation indirectly improved self-acceptance and environmental mastery. Moderation analyses indicated that baseline anxiety and depression levels influenced the intervention’s effectiveness, with fewer symptom levels associated with better emotional outcomes post-intervention. The game received positive user feedback, particularly regarding its psychoeducational content and emotional awareness components.DiscussionWhile emoWELL shows promise as a preventive tool for emotion regulation in emerging adults with low emotional symptomatology, its effectiveness may be limited for those with elevated anxiety and depression levels, suggesting its optimal use as a complementary tool under professional supervision or in university settings with appropriate support.